Activation of Liver X Receptor Improves Viability of Adipose-Derived Mesenchymal Stem Cells to Attenuate Myocardial Ischemia Injury Through TLR4/NF-κB and Keap-1/Nrf-2 Signaling Pathways - Wang, Yabin (Antioxid Redox Signal, 2014)
Aims: Clinical application of cellular therapy for cardiac regeneration is significantly hampered by the low retention of engrafted cells, mainly attributable to the poor microenvironment dominated by inflammation and oxidative stress in the host's infarcted myocardium. This study aims at investigating whether liver X receptor (LXR) agonist T0901317 will improve survival of adipose-derived mesenchymal stem cells (AD-MSCs) after transplantation into infarcted hearts. Results: Noninvasive in vivo bioluminescence imaging and histological staining showed that LXR agonist T0901317 improved the retention and survival of intramyocardially injected AD-MSCs. Moreover, combined therapy of LXR agonist and AD-MSCs inhibited host cardiomyocyte apoptosis, reduced fibrosis, and improved cardiac function, while it concomitantly decreased inflammatory cytokines (e.g., tumor necrosis factor-α and interleukin-6) and increased growth factor (e.g., vascular endothelial growth factor and basic fibroblast growth factor) expression in infarct myocardium. To reveal possible mechanisms, AD-MSCs were subjected to hypoxia/serum deprivation (H/SD) injury to simulate ischemic conditions in vivo. The LXR agonist (10(−7) mM) improved AD-MSC survival under H/SD condition. Western blot revealed that the LXR agonist reduced TLR4, TRAF-6, and MyD88 protein expression, inhibited IκBα phosphorylation and NF-κB-p65 nuclear translocation, which resulted in accelerated Keap-1 protein degradation, enhanced Nrf-2 nuclear translocation, and increased HO-1 protein expression. Innovation and Conclusion: LXR agonist can enhance the functional survival of transplanted AD-MSCs in infarcted myocardium, at least partially, via modulation of the TLR4/NF-κB and Keap-1/Nrf-2 signaling pathways. Moreover, combined therapy of LXR agonist and AD-MSCs has a synergetic effect on cardiac repair and functional improvement after infarction. Antioxid. Redox Signal. 21, 2543–2557.